Imagining the metaverse court: a conversation between science fiction and Shakespeare - Tait, David; Rossner, Meredith (Frontiers in Sociology, 2025)
This article explores the concept of a metaverse courtroom by engaging in an imaginative dialogue between Shakespeare's Hamlet and Neal Stephenson's Snow Crash. Using Connolly's method of juxtaposing distinct intellectual traditions, the analysis examines key aspects of justice processes—presence, facework, movement, adversarialism, and evidence presentation—in virtual spaces. Drawing on insights from dramaturgy, the sociology of emotions, and science fiction, the article considers how the performative and symbolic dimensions of physical courtrooms might translate to the metaverse. By imagining the metaverse courtroom as a space for innovation and interaction, this article seeks to illuminate how literature, sociology, and technology can collaboratively inspire the reimagining of justice in virtual environments.